Kebenaran Pesan Dakwah - Aziz, Moh. Ali (Departement of Islami Comuunication and Broadcasting, Faculty of Da'wah and Communication, State Islamic University of Sunan Ampel (UINSA) Surabaya Indonesia, 2014)
The truth constitutes the object study for centuries. Philosophy, science and religion present as the way to find the truth. However, the truth found by the human beings is miscellaneous depends on the human condition such as circumstances of social-culture surrounding, mindset, as well as the faith. Therefore, there are many theories of truth. In Da’wah, the messages must be the truth, both its existence and content. Similarly, methods and media of Da’wah must walk in the truth, especially the approach to the partner of Da’wah. It may be said that the whole process to Da’wah activities should contain the element of truth.Keywords: Truth, the messages of Dakwah, Islamic philosophy———————————————————————-Kebenaran merupakan obyek pencarian manusia selama berabad-abad. Filsafat, ilmu dan agama hadir sebagai jalan manusia untuk menemukan kebenaran. Namun, kebenaran yang ditemukan manusia menjadi beragam sangat tergantung dengan kondisi manusia: keadaan sosial budaya yang melingkupinya, pola pikir, serta keyakinan yang di–anutnya. Karenanya, muncul banyak teori kebenaran. Dalam dakwah, pesan yang disampaikan harus berupa kebenaran, baik eksistensi maupun substansinya. Demikian pula, me–tode dan media dakwah harus berjalan dalam rambu kebenaran, terutama pendekatan kepada mitra dakwah. Boleh dikatakan bahwa seluruh proses sampai akhir aktifitas dakwah harus mengandung unsur kebenaran.Kata Kunci: Kebenaran, pesan dakwah, filsafat Islam